Exploring the Impact of Gamification and Relationship Marketing on Gen Z Loyalty: Evidence from Indonesian Culinary MSMEs - Alberta Adinata; Budi Eko Soetjipto (International Journal of Economics and Management Sciences, 2025)
In the face of an increasingly competitive landscape, culinary MSMEs in Indonesia are required to not only offer quality products, but also create interactive and emotional consumer experiences. This study aims to investigate the mediating role of loyalty programs in influencing the relationship between gamification and relationship marketing on Gen Z consumer loyalty. Using a quantitative approach through online questionnaire distribution to 385 Gen Z respondents on social media, the results show that both gamification and relationship marketing have a significant direct influence on consumer loyalty, as well as an indirect influence through the mediation of loyalty programs. The findings confirm that the integration of gamification elements-such as challenges, point systems, and leaderboards-in loyalty programs can generate intrinsic motivation that strengthens consumers' emotional engagement. Meanwhile, a relationship marketing approach based on trust and personalization encourages long-term commitment. This research extends the application of the Commitment-Trust and Self-Determination theories in the digital-native context, and makes a conceptual contribution to the strategic design of experiential loyalty programs for culinary MSMEs targeting Gen Z consumers. The practical implication is that business owners need to build a loyalty ecosystem that is not only functional, but also fun and emotionally meaningful.